Contribution of Social Media to the Growth of Small and Medium Enterprises in Chitwan - Dahal Chhetri, Ashmita (AMC Journal, 2024)
This study's primary goal is to investigate how social media affects the expansion of small businesses and medium enterprises, with a particular emphasis on Small and Medium Enterprises (SMEs) in Chitwan. A descriptive and causal-comparative analysis was used in this study. The study's demographic consists of all Chitwan SME owners who use social media to market their goods and services. A total of 160 responders were chosen through the application of the purposive sampling technique. A standardized questionnaire that was individually presented was used to conduct a survey and gather the primary data needed for the investigation. In this study, statistical methods such as regressions, correlation, mean, and standard deviation were employed. The reliability has been tested using Cronbach’s alpha. Social media marketing, social media personalization, and social media customer service are the independent variables. Social media-driven business growth is a dependent variable. The respondents most strongly agreed that social media is one of the most crucial components of business growth. Pearson’s correlation coefficient indicates a positive correlation between the independent variable of social media marketing and the dependent variable of small and medium-sized business growth. The dependent variable of small and medium-sized business growth and social media customer service suggest a positive correlation. The results indicate that social media customer service and the expansion of SMEs are significantly correlated.